2009
DOI: 10.1021/ma901607w
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature, Aqueous-Phase Fabrication of Poly(methacrylic acid) Brushes by UV-LED-Induced, Controlled Radical Polymerization with High Selectivity for Surface-Bound Species

Abstract: Poly(methacrylic acid) (PMAA) brushes were grafted from Si/SiO2 substrates by means of immobilized-photoiniferter-mediated controlled radical polymerization. The employed UV setup was based on ultraviolet light-emitting diodes (UV-LEDs), which allowed for a precise control of the brush height with irradiation time, as observed by in situ quartz crystal microbalance experiments with dissipation monitoring (QCM-D). In contrast to many alternative approaches, it was shown that the novel UV source in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 53 publications
3
73
0
1
Order By: Relevance
“…PDMS samples were prepared with a Sylgard® 184 kit (Dow Corning, Midland, MI) according to a standard procedure [5,6]. The diameter/thickness of disk was 30/5 mm and the radius of pin was 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…PDMS samples were prepared with a Sylgard® 184 kit (Dow Corning, Midland, MI) according to a standard procedure [5,6]. The diameter/thickness of disk was 30/5 mm and the radius of pin was 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Spencer et al have used a photoinduced "grafting from" approach to grow polymethacrylic acid (PMAA) brushes on Si/SiO 2 surfaces, and investigated the lubrication properties of the PMAA brushes of different molecular weights and soft, hydrophilic ox-PDMS pins in macroscopic tribological experiments under lowcontact-pressure, aqueous conditions [36]. The results showed that the PMAA brushes could not be distinguished from the μ vs. sliding speed plots, and long-term stability of the short 15 nm PMAA brushes showed to be inferior to that of long brushes (240 nm dry thickness).…”
Section: Improved Aqueous Lubrication By Surface Grafted Polymer Brushesmentioning
confidence: 99%
“…21. [279][280][281] The mechanism in which solvated polymer brushes lubricate is thought to be as follows. 27 Tribological studies were conducted using a ball on disk NTR2 tribometer in a reciprocating motion over 120 with the speed change being controlled sinusoidally.…”
Section: Polymer Brushes On Silicon Wafers For Tribological Applicationsmentioning
confidence: 99%